Research on Modeling and Simulation of Mixed EMI Filter (Kongzhi Yu Xinxi Jishu)
By applying the transformation principle of branches equivalent impedance and optimizing the model structure of mixed EMI filter, a transfer function model of mixed EMI filter is obtained and the key factors to affect EMI filter’s performance are analyzed. Validity of the model is proved by the comparison between simulation results and calculation ones.